2013
DOI: 10.1095/biolreprod.112.105619
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cholesterol Transport by Insulin-Treated Gestational Diabetes Mellitus in Human Full-Term Placenta1

Abstract: Gestational diabetes mellitus (GDM) is a common complication of pregnancy that is characterized by glucose intolerance, leads to dyslipidemia, and is aggravated by obesity. Cholesterol is taken up by the placenta as part of lipoproteins through the scavenger receptor class B type I receptor (SRBI), low-density lipoprotein receptor (LDLR), and very low density lipoprotein receptor (VLDLR), and its efflux is then mediated by ABCA1 and ABCG1. PCSK9 is involved in the degradation of LDLR and VLDLR. The goal of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 58 publications
5
40
0
Order By: Relevance
“…Moreover, cholesterol transfer from the maternal to the neonatal circulation via the placenta might be also affected by GDM through the modulation of the expression of key receptors. Dubé et al suggested that reduced expression of ABCG1 in GDM pregnancies could be part of a compensatory mechanism to limit excessive transfer of cholesterol to the neonatal circulation; in addition, the decreased expression of ABCA1 could reflect an accumulation of cholesterol into the placenta even if the placental weight does not change in GDM pregnancies [31]. This could explain why the levels of total cholesterol, HDL, and LDL were not affected in cord blood of GDM pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cholesterol transfer from the maternal to the neonatal circulation via the placenta might be also affected by GDM through the modulation of the expression of key receptors. Dubé et al suggested that reduced expression of ABCG1 in GDM pregnancies could be part of a compensatory mechanism to limit excessive transfer of cholesterol to the neonatal circulation; in addition, the decreased expression of ABCA1 could reflect an accumulation of cholesterol into the placenta even if the placental weight does not change in GDM pregnancies [31]. This could explain why the levels of total cholesterol, HDL, and LDL were not affected in cord blood of GDM pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the reduction of placental ABCA1 mRNA has already been reported in obese and normal weight subjects with IGT and suggested to impair placental cholesterol-uptake and transport. 38 Although ABCA1 Figure 2. Placental ABCA1-cpG5 and -cpG6 DNa methylation levels according to maternal and newborn metabolic profile.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid modifications were not as common in placentae from women with type 1 253 diabetes and there was preferential activation of glycosylation and acylation pathways. In 254 term placentae from normal weight or overweight/obese women with GDM, there were 255 variable effects on lipid pathways depending on BMI category, including alterations in the 256 expression of SRBI, LDLR, VLDLR, ABCA1, ABCG1, and proprotein convertase subtilisin/kexin 257 type 9 [77]. 258…”
Section: Pre-existing Diabetes and Gdm 234 235mentioning
confidence: 99%